Pyrazinamide Induced Parkinsonism (Journal of Medicine, 2017)
Parkinsonism refers to a syndrome characterized by the presence of tremor, rigidity and bradykinesia. In addition there is loss of postural reflexes as well as freezing. Drugs rank the second in the causes of parkinsonism. As it is reversible, drug-induced parkinsonism (Rabbit syndrome) should be borne in mind and suspected in any patient receiving drug treatment. We report a case of drug induced parkinsonism, evidently due to pyrazinamide. To the best of our knowledge, this is the first case to be reported in our country.J MEDICINE January 2017; 18 (1) : 42-43